Measuring the achievements of smart economics in the smart village program in Lampung Province 2020-2024 - Endriyon, Endriyon; Gunarto, Toto; Murwiati, Asih (Studi Ekonomi dan Kebijakan Publik, 2024)
Purpose: This study aims to measure the impact of Smart Village dimensions on rural community welfare in Lampung Province (2020–2024), with a particular focus on the Smart Economy pillar and its integration with digital transformation and technosociopreneurship. Research/methodology: A quantitative approach was employed using multiple linear regression (Ordinary Least Squares) on data collected from 70 Smart Village locations across four districts in Lampung. The independent variables included six Smart Village dimensions: Smart People, Smart Governance, Smart Mobility, Smart Environment, Smart Living, and Smart Economy. The dependent variable was community welfare. Instrument testing and classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) were conducted to validate the model. Results: All six Smart Village dimensions showed a significant positive influence on community welfare. The Smart People dimension had the strongest effect (coefficient = 0.8489). The regression model demonstrated high explanatory power (R² = 0.9535) and satisfied all classical assumptions. Notably, Smart Economy initiatives—such as MSME digitalization, inclusive market access, and technology-based entrepreneurship—directly contributed to increased income, employment opportunities, and local economic growth. Conclusions: The application of Smart Village principles, particularly in economic transformation, significantly enhances rural welfare. Digital innovation, governance quality, and community capacity-building are critical drivers of inclusive development and service improvement. Limitations: The study is limited to Lampung Province and lacks comparative data from other regions. It also does not assess long-term or behavioral impacts. Contribution: This research provides empirical support for Smart Village policies, guiding investments in digital infrastructure, entrepreneurship training, and multi-stakeholder collaboration for rural development.